2018
DOI: 10.1002/jso.25174
|View full text |Cite
|
Sign up to set email alerts
|

A preoperative prognostic model to predict surgical success in patients with perihilar cholangiocarcinoma

Abstract: Surgical success was achieved in only 30% of patients with PHC undergoing exploratory laparotomy and could be predicted by age, cholangitis, hepatic artery involvement, lymph node metastases, and Blumgart stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…These incidences are in contrast to 6.2%, 8 17%-45%, 2,11 and 23% 21 respectively, in Western countries. Nonetheless, our resectability rate of 69.7% exceeded that in other studies, 22,23 which can be explained by the proactive use of left hepatic trisectionectomy, hepatic artery resection, or pancreatoduodenectomy for locally advanced tumors, 16,24 as is common in Japan. 7 Otherwise, considerable numbers of patients would have been treated as unresectable.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…These incidences are in contrast to 6.2%, 8 17%-45%, 2,11 and 23% 21 respectively, in Western countries. Nonetheless, our resectability rate of 69.7% exceeded that in other studies, 22,23 which can be explained by the proactive use of left hepatic trisectionectomy, hepatic artery resection, or pancreatoduodenectomy for locally advanced tumors, 16,24 as is common in Japan. 7 Otherwise, considerable numbers of patients would have been treated as unresectable.…”
Section: Discussioncontrasting
confidence: 70%
“…There are some studies proposing a new preoperative staging scheme to stratify survival, 21,22,25 most of which involve radiologic findings, including tumor diameter and conditional factors, as determinants. Thus, tumor size is a well‐known prognostic factor in perihilar cholangiocarcinoma and a major selection criterion for liver transplantation 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“… 17 Considering the 310 resections performed over 9 years in this study, the number of pCCA per center per year is estimated at 2 to 3 procedures. Since there are a few Dutch centres that report an annual higher volume of pCCA resections, 18 , 19 the number of resections in some centres is likely much less that the annual 2 to 3. Mortality rate within 90‐days after surgery was 14% in this nationwide study, which corresponds to the mortality reported in series from experienced Western centres.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion of these patients with regional experts in might increase the accuracy of staging, currently about half of all patients who undergo explorative surgery are found to have unresectable disease. 18 , 29 , 30 Regional multidisciplinary meetings might help to increase the number of patients referred for curative resection, but also help select patients that might be eligible for palliative systemic therapy or other experimental palliative local therapies. Further centralization of the resection for pCCA that are currently performed across 14 centres to a handful of hospitals might help to decease the 90‐day mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Finally, resection of pCCA is high-risk surgical procedure with a postoperative 90-day mortality rate between 5 and 18% in Western series, [12][13][14][15] and as such the possible benefit does not outweigh the risks in patients with advanced age, serious co-morbidity, or frailty. [16][17][18] The Mayo Clinic and several other centers in the United States and Europe are currently treating a select subgroup of patients with locally advanced pCCA with neoadjuvant chemoradiation and liver transplantation (LT). [19][20][21] In patients treated according to this protocol, a 5-year survival of 53%, slightly superior to the survival of patients after surgery for resectable disease, could be achieved.…”
mentioning
confidence: 99%